Sarkopenia pada Lanjut Usia: Patogenesis, Diagnosis dan Tata Laksana - Njoto, Edwin Nugroho; Suka Aryana, I Gusti Putu (UI Scholars Hub, 2023)
‘Sarcopenia’ involves a progressive age-related loss of muscle mass and associated muscle weakness that renders frail elders susceptible to serious injury from sudden falls and fractures and losing their functional independence. This disease has a complex multifactorial pathogenesis, which involves not only age-related changes in neuromuscular function, muscle protein turnover, and hormone levels and sensitivity, but also a chronic pro-inflammatory state, oxidative stress, and behavioral factors – in particular, nutritional status and degree of physical activity. In the previous definition by the European Working Group on Sarcopenia in Older People (EWGSOP) in 2010, the diagnosis of sarcopenia requires the presence of both low muscle mass and low muscle function. Since the 2010 definition is difficult to be translated to clinical practice, the EWGSOP uses low muscle strength as the primary parameter of sarcopenia in the 2018 definition; sarcopenia is probable when low muscle strength is detected. A sarcopenia diagnosis is confirmed by the presence of low muscle quantity or quality. When low muscle strength, low muscle quantity/quality and low physical performance are all detected, sarcopenia is considered severe. According to the pathophysiological factors involved in the pathogenesis of sarcopenia, different treatment strategies against sarcopenia are resistance exercise training, increase essential amino acids intake, vitamin D supplementation for those with vitamin D deficiency, polyunsaturated fatty acids (PUFAs) supplementation, testosterone supplementation, angiotensin-converting enzyme inhibitor administration.